Dissipative coupling for the seismic enhancement of adjacent structures. (15th November 2019) - Gattulli, Vincenzo; Potenza, Francesco; Di Sabatino, Umberto
Highlights: New design methods for the seismic improvements of coupled adjacent structures. New performance index to evaluate the effectiveness of the coupled system. Case study of the Edifice A of the Faculty of Engineering of University of L'Aquila. Abstract: The paper suggests a procedure for the seismic improvement of adjacent structures. The control strategies that constitute the core of the methodology are based on the performance of a simple linear analytical model composed by two simple oscillators linked by a dissipative element. The constitutive behavior of the dissipative connection is described by a Kelvin-Voigt model. For such system, have been defined some optimal configurations depending by the eigenvalue coalescence or by the stochastic linear response. The use of simplified model can provide a rapid and well-approximate choice of the dampers mechanical characteristics. Moreover, the procedure will offer a varied scenario of possibilities where the optimal choice will depend also by the aim to be achieved (e.g. minimum of accelerations or displacements). In particular, has been proposed a new weighted performance that take into account the cost and energy issued by the damper helping the designer in the choice of the best damper. The final step is related to a refinement of the parameter selection through a nonlinear analysis. Such approach has been adopted for the seismic improvements of the Edifice A of the Faculty of Engineering of University of L'Aquila heavily destroyed during the 2009 L'Aquila Earthquake, here reported as case study.